Antenatal Micronutrient Supplementation Relationship with Children's Weight and Height from Birth up to the Age of 18 Months. - Hossein Jabbari; Fariba Bakhshian; Mohammad Asgari; Mohammadreza Sattari; Mohammad Naghavi-Behzad; Simin Ozar Mashayekhi (Tehran University of Medical Sciences, 2013)
Maternal nutritional is the most important environmental factor influencing pregnancy outcome. While studies showed association between maternal iron-micronutrient deficiencies with pregnancy outcome, data examining impact of micronutrient supplementation on growth rate beyond birth are sparse. Present study examined the relationship between iron and multivitamins supplementation on growth rate of babies up to age of 18 month.This study was a statistical analysis on data recorded through a routine procedure in health houses from 1994 to 2007. Subjects were selected by a two-stage randomization method and required data extracted from the records. Analyses were performed using STATA 10 software.Data was collected for 3835 pairs of mother-baby. Mothers received 61.7±5.4 and 115.6±53.8 multivitamins and iron tablets, respectively. Analyses showed significant relationship between children's weight and height at birth with iron supplementation and children's height at 6, 12 and 18 month with multivitamins supplementation.Mechanisms of these effects are unclear but it is safe to suggest supplementation during pregnancy is necessary.